2019
DOI: 10.32918/nrs.2019.1(81).07
|View full text |Cite
|
Sign up to set email alerts
|

Analysis of Reliability-Critical Hydraulic Impact Conditions at WWER-1000 NPP Active Safety Systems

Abstract: An original method to determine the onset of conditions for reliabilitycritical hydraulic impacts for reliability analysis of active safety systems of nuclear power installations is proposed. The suggested method is based on determining the effect of head-flow characteristic delay onto hydraulic impact preconditions during the changes of pipeline system hydrodynamic parameters under transitional modes (e.g. in pump start-up). The delay time of responses to change in the hydrodynamic system parameters embodies … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
8
0
5

Year Published

2022
2022
2024
2024

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 7 publications
(13 citation statements)
references
References 2 publications
0
8
0
5
Order By: Relevance
“…The method is based on the fundamental thermodynamic principles of analysis of the influence of fluctuating pressure and flow disturbances in PSS-NC circuits on the conditions and consequences of THI in the process of accidents with circulation circuit leaks. According to these principles, if pressure and mass increase (or decrease) simultaneously and independently of each other in an equilibrium system, the system is unstable [9][10][11][12].…”
Section: The Methods Of Determining the Criteria And Terms Of Thi In ...mentioning
confidence: 99%
See 1 more Smart Citation
“…The method is based on the fundamental thermodynamic principles of analysis of the influence of fluctuating pressure and flow disturbances in PSS-NC circuits on the conditions and consequences of THI in the process of accidents with circulation circuit leaks. According to these principles, if pressure and mass increase (or decrease) simultaneously and independently of each other in an equilibrium system, the system is unstable [9][10][11][12].…”
Section: The Methods Of Determining the Criteria And Terms Of Thi In ...mentioning
confidence: 99%
“…-Negative consequences for the reliability/safety of NPPs of this type of THI in PSB-PC can be: violation of safety functions for emergency cooling of the active zone of reactors and refueling of steam generators, hydrodynamic and thermal shocks in systems important for safety, etc. [9][10][11][12].…”
Section: Introductionmentioning
confidence: 99%
“…Модернізація стратегій і систем управління аваріями на ядерних енергоустановках з їх повним тривалим знеструмленням (12) Рівняння руху живильної води у системі АЖНПП ПГ із загальною довжиною трубопроводу L: (13) Рівняння руху пари в паропроводі від ПГ:…”
Section: методи кваліфікації ажнпп пг на внутрішні умови аварій з птзunclassified
“…One of the current approaches to improve the efficiency of nuclear power plant (NPP) operation is to increase the depth of nuclear fuel (NF) burnup [1 -7] and others. Increasing the depth of nuclear fuel burnup (DNFB) can be achieved by modernizing the thermophysical properties of NF, in particular, in well-known experimental studies, reviewed, for example, in [8]; it was found that DNFB ~ n F −  ( 0 n  , F  is the parameter of thermal conductivity of NF).…”
Section: Introductionmentioning
confidence: 99%
“…Thus, an "artificial" decrease in core thermal conductivity NF increases DNFB (ceteris paribus). In practice, an "artificial" decrease in F  can be achieved by chemically adding to NF elements with reduced thermal conductivity [8]. The consequence of a relative decrease in F  (ceteris paribus) is a relative increase in temperature of NF ( ) F T and, accordingly, in DNFB.…”
Section: Introductionmentioning
confidence: 99%